2017
DOI: 10.7717/peerj.3115
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional survey on health-related quality of life of elementary school students using the Korean version of the EQ-5D-Y

Abstract: Background and ObjectiveThe Korean version of the EQ-5D-Y was launched in 2015 by the EuroQol group. Currently, there is no HRQOL data obtained by using the EQ-5D-Y in Korea. This study aimed to measure health-related quality of life of Korean elementary school students using the EQ-5D-Y.MethodsElementary school students were recruited from 11 primary schools in Gyungbuk, South Korea. The EQ-5D-Y was self-administered in the sample population. Demographic characteristics were collected from the subjects’ paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
7
11
1
Order By: Relevance
“…Adolescents with one or both parents unemployed reported worse health status. This is in line with previous studies, where children from families with the lowest household income showed the lowest VAS index scores, and children with parents with the lowest educational level reported more problems in the EQ-5D-Y-3L dimensions [ 28 , 29 ]. If adolescents are able to report their parents’ occupational status in a reliable matter can be discussed and might be a limitation of our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Adolescents with one or both parents unemployed reported worse health status. This is in line with previous studies, where children from families with the lowest household income showed the lowest VAS index scores, and children with parents with the lowest educational level reported more problems in the EQ-5D-Y-3L dimensions [ 28 , 29 ]. If adolescents are able to report their parents’ occupational status in a reliable matter can be discussed and might be a limitation of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Despite that the present study was conducted among a general population of adolescents, more than half of all respondents reported problems in at least one of the EQ-5D-Y-3L dimensions which was higher than observed earlier [ 29 ]. The age range of participants in our study could explain these findings, as it is recognized that adolescents go through several life-challenging changes e.g.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations